The possibilities of treatment of stormwater polluted with bofuels in the lamella oil separator = Możliwości oczyszczania w separatorze lamelowym ścieków opadowych zanieczyszczonych biopaliwami - Bering, Sławomira; Iżewska, Anna; Mazur, Jacek; Tarnowski, Krzysztof; Treichel, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Laboratory tests were conducted simulating the process of polluting stormwater with fuels and afterwards treating this sewage in the separator of oil derivative substances. The diesel oil - ON and the pure biofuel - BIO 100, available on the market, were the subject of the tests.
Keywords: ścieki opadowe; biopaliwo; zanieczyszczenia; substancje ropopochodne; separator lamelowy; stormwater; biofuel; oil derivative substances; separators